Correlates of same-sex behavior disclosure to health care providers among Black MSM in the United States: Implications for HIV prevention - Sun, Christina J. (AIDS Care, 2018)
Disclosure of same-sex behavior to health care providers (HCPs) by men who have sex with men (MSM) has been argued to be an important aspect of HIV prevention. However, Black MSM are less likely to disclose compared to white MSM. This analysis of data collected in the United States from 2006-2009 identified individual and social network characteristics of Black MSM (n=226) that are associated with disclosure that may be leveraged to increase disclosure. Over two-thirds (68.1%) of the sample had ever disclosed to HCPs. Part-time employment (AOR=0.32, 95% CI=0.11-0.95), bisexual identity (AOR=0.29, 95% CI=0.12-0.70), and meeting criteria for alcohol use disorders (AOR=0.32, 95% CI=0.14-0.75) were negatively associated with disclosure. Disclosers were more likely to self-report being HIV-positive (AOR=4.47, 95% CI=1.54-12.98), having more frequent network socialization (AOR=2.15, 95% CI=1.24-3.73), and having a social network where all members knew the participant had sex with men (AOR=4.94, 95% CI=2.06-11.86). These associations did not significantly differ by self-reported HIV status. Future interventions to help MSM identify social network members to safely disclose their same-sex behavior may also help disclosure of same-sex behavior to HCPs among Black MSM.